Decision Support Information System Promotion of Job Position using Profile Matching Method (Case Study: Hotel Surya Yudha Purwokerto) - Chandra Kesuma; Trias Nur Maulani - Universitas BSI (Indonesian Journal of Networking and Security (IJNS), 2022)
Abstract - The company at all times carries out promotions for employees. This takes a long time and is said to be less effective and efficient to assess the performance of employees who will be promoted if done manually. This Decision Support System can be used as an alternative in processing employee assessment systems that are still manual. The system is intended to be a tool to help simplify and speed up the assessment process for promotion. The process uses a method called profile matching. Profile matching is also known as gap. The final result of the profile matching itself is in the form of ranking. Keywords : Decision Support Information System, Promotion, Profile Matching Method Abstrak – Perusahaan setiap waktu melakukan kenaikan jabatan bagi karyawan. Hal ini membutuhkan waktu yang lama dan dikatakan kurang efektif dan efisien untuk menilai kinerja karyawan yang akan dinaikan jabatannya jika dilakukan secara manual. Sistem Pendukung Keputusan ini bisa digunakan sebagai alternatif dalam pengolahan sistem penilaian karyawan yang masih manual. Sistem ini dimaksudkan untuk menjadi alat untuk membantu mempermudah dan mempercepat proses penilaian untuk kenaikan jabatan. Prosesnya menggunakan metode yang disebut profile matching. Profile matching disebut juga dengan istilah gap. Hasil akhir dari profile matching itu sendiri berupa ranking. Kata Kunci : Sistem Informasi Pendukung Keputusan, Kenaikan Jabatan, Metode Profile Matching